Three mathematical statements are given to find the values of $x$ and $y$ in this logarithm problem.

$(1) \,\,\,\,\,\,$ $z^3 = \sqrt{36^5}$

$(2) \,\,\,\,\,\,$ $x = \log_{6} (z) -\dfrac{2}{3}$

$(2) \,\,\,\,\,\,$ $y = x^{-5}$

The first statement expresses the value of $z$ in terms of a radical having an exponential term as its radicand. The second statement is useful to find the value of $x$ by substituting the value of $z$ in it. Finally, the third statement is useful to find the value $y$ by substituting the value of $x$ in it.

Solve the first statement and find the value of $z$.

$z^3 = \sqrt{36^5}$

$\implies z^3 = \sqrt{{(6^2)}^5}$

Apply the power rule of an exponential term to simplify this expression.

$\implies z^3 = \sqrt{6^{2 \times 5}}$

$\implies z^3 = \sqrt{6^{5 \times 2}}$

$\implies z^3 = \sqrt{{(6^5)}^2}$

$\implies z^3 = 6^5$

Take cube root both sides to find the value of $z$.

$\implies \sqrt[\displaystyle 3]{z^3} = \sqrt[\displaystyle 3]{6^5}$

$\therefore \,\,\,\,\,\, z = {(6)}^{\dfrac{5}{3}}$

Now, substitute the value of $z$ in the second statement to obtain the value of $x$.

$x = \log_{6} (z) -\dfrac{2}{3}$

$\implies x = \log_{6} {(6)}^{\dfrac{5}{3}} -\dfrac{2}{3}$

Use the power law of logarithm of an exponential term to simplify the equation.

$\implies x = \dfrac{5}{3} \log_{6} 6 -\dfrac{2}{3}$

According to logarithm of base rule, the logarithm of a number to same number is one.

$\implies x = \dfrac{5}{3} \times 1 -\dfrac{2}{3}$

$\implies x = \dfrac{5}{3}-\dfrac{2}{3}$

$\implies x = \dfrac{5-2}{3}$

$\implies x = \dfrac{3}{3}$

$\therefore \,\,\,\,\,\, x = 1$

Now substitute the value of $x$ in third algebraic equation to get the value of $y$.

$y = x^{-5}$

$\implies y = {(1)}^{-5}$

$\therefore \,\,\,\,\,\, y = 1$

Therefore, it is derived that value of $x$ is equal to the value of $y$ and it is $1$. It is written as $x = y = 1$

List of most recently solved mathematics problems.

Jul 04, 2018

Limit (Calculus)

Evaluate $\displaystyle \large \lim_{x \,\to\, \tan^{-1}{3}} \normalsize {\dfrac{\tan^2{x}-2\tan{x}-3}{\tan^2{x}-4\tan{x}+3}}$

Jun 23, 2018

Limit (Calculus)

Evaluate $\displaystyle \large \lim_{x \to 0} \normalsize \dfrac{e^{x^2}-\cos{x}}{x^2}$

Jun 22, 2018

Integral Calculus

Evaluate $\displaystyle \int \dfrac{1+\cos{4x}}{\cot{x}-\tan{x}} dx$

Jun 21, 2018

Limit

Evaluate $\displaystyle \large \lim_{x \to \infty} \normalsize {\sqrt{x^2+x+1}-\sqrt{x^2+1}}$

Math Doubts is a best place to learn mathematics and from basics to advanced scientific level for students, teachers and researchers.
Know more

Learn how to solve easy to difficult mathematics problems of all topics in various methods with step by step process and also maths questions for practising.